Multi-Objective Optimization for Stabilized Subgrade Soil through Performance Index and Taguchi Integrated Best-Worst Optimization Technique - Kumar, Amit; Jain, Ashwani (International Journal of Integrated Engineering, 2025)
The multi-objective optimization of a project involving number of performance characteristics is always a complicated task. Present article demonstrates two different multi-objective optimization approaches to fill the gap of non-availability of multi-objective optimization option in a popular design of experiments-based optimization technique i.e., Taguchi method. Though both approaches use the weightage criteria but have their own pros and cons over each other. First approach namely Performance Index method follows the numeric methods and could perform independently while second is an improvement over traditional Taguchi method and could be coupled with predefined robust Design of Experiments. The analytical results have been found compliance with the attainment of optimal design mixtures accordance to performance characteristics preferences. The demonstration of the techniques has addressed the drawbacks of the traditional Taguchi method over novel Best-Worst method. Results have shown that significant improvement in total quality of stabilized subgrade soil could be achieved by assigning appropriate weightage to factors and quality characteristics.